2002
DOI: 10.1523/jneurosci.22-05-01629.2002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Centrally Located Gate in the Pore of a Serotonin-Gated Ion Channel

Abstract: Serotonin-gated ion channels (5-HT3) are members of the ligand-gated channel family, which includes channels that are opened directly by the neurotransmitter acetylcholine, GABA, glycine, or glutamate. Although there is general agreement that the second transmembrane domain (M2) lines the pore, the position of the gate in the M2 is less certain. Here, we used substituted cysteine accessibility method (SCAM) to provide new evidence for a centrally located gate that moves during channel activation. In the closed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
81
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 42 publications
9
81
0
Order By: Relevance
“…Such Cd 2ϩ binding sites have been introduced into other proteins, such as K ATP channels, voltage-gated K ϩ channels, and glutamate transporters (30 -33). Previously, we determined the structure of the M2 and the location of the gate using cysteinesubstituted 5-HT 3A receptors (9). Using these cysteine-substituted receptors, we now demonstrate that the selectivity filter of the 5-HT 3A receptor is sufficiently narrow to form high affinity Cd 2ϩ binding sites.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Such Cd 2ϩ binding sites have been introduced into other proteins, such as K ATP channels, voltage-gated K ϩ channels, and glutamate transporters (30 -33). Previously, we determined the structure of the M2 and the location of the gate using cysteinesubstituted 5-HT 3A receptors (9). Using these cysteine-substituted receptors, we now demonstrate that the selectivity filter of the 5-HT 3A receptor is sufficiently narrow to form high affinity Cd 2ϩ binding sites.…”
mentioning
confidence: 78%
“…Molecular Biology-Cysteine mutants of 5-HT 3A were constructed previously (9). Four mutants (L8ЈC, G10ЈC, Y11ЈC, F14ЈC) were not tested because they yielded little or no currents when expressed alone (see Ref.…”
Section: Methodsmentioning
confidence: 99%
“…Position 15′ of the 5-HT 3A receptors TM2 domain is a non-pore-facing amino acid residue (Reeves et al, 2001;Panicker et al, 2002). In addition to its role in channel gating, the amino acid residue at 15′ also appears to have important roles in channel modulation by alcohol and anesthetics (Mihic et al, 1997;Wick et al, 1998), and binding of these drugs to a hydrophobic pocket involving this residue alters receptor function.…”
Section: Discussionmentioning
confidence: 99%
“…Residue L293 is in the same 15′ position as a residue in the GABA A receptor that has important roles in channel gating (Findlay et al, 2001;Scheller & Forman, 2002) and modulation by alcohols and general anesthetics (Mihic et al, 1997;Wick et al, 1998). This amino acid residue is thought to reside on the non-porefacing side of TM2 domain (Panicker et al, 2002;Reeves et al, 2001). We recently demonstrated that alcohol enhancement of 5-HT 3A receptor-mediated current was abolished with L293C and L293S mutations (Hu et al, 2006).…”
Section: Role Of L293 In the Modulatory Action Of 5-himentioning
confidence: 99%
“…7D). In future studies, it should be feasible to employ the substituted cysteine accessibility method to identify all residues within the MA stretch that impinge upon the permeation pathway in a manner analogous to that adopted to evaluate the channel-lining TM2 residues of, for example, the 5-HT 3A receptor (18,19).…”
Section: Discussionmentioning
confidence: 99%